Oppression and Defiance: A Feministic Analysis of Khalid Hosseini’s Novel A Thousand Splendid Suns - Muhammad Safyan; Hifsa Faiz; Aysha Khalik; Adeeba Manzoor (`, 2025)
This paper examines women’s systemic oppression and empowerment under Taliban rule in Khalid Hosseini’s novel A Thousand Splendid Suns. It analyzes the intersecting chords of power, patriarchy, oppression and liberation. The concept of suppression of French feminist Simon De Beauvoir is used as a framework for the analysis of the text. By keeping in view the feminist framework, the study explores the journey of two female protagonists and their forced marriage, domestic abuse, Taliban’s oppression and their ultimate empowerment. Despite vitriol conditions, their lives are filled with moments of resistance, solidarity, rebellion against patriarchy and women’s empowerment. They make education and mutual love their strength and found their identity. Deep reading of the text of the novel is used as a primary resource, while articles, interviews and different books are used as secondary resources of the text. This study is significant as it explores and highlights the effects of oppression, patriarchy and empowerment. Using the qualitative analysis, the study criticizes the systemic oppression of woman and the need for their liberation in the face of darkness. Keywords: Oppression, Feminism, Khalid Husseini, Thousand Splendid Suns